Leadership Through Social Media: Local Government Strategies for Innovation, Transparency, and Public Participation (A Study in Denpasar City, Bali) - Tri Putri Andriastuti, Komang; Ayu Yuliartika Dewi, I Gusti Agung (Indonesian Association for Public Administration (IAPA), 2025)
Leadership in the digital era requires not only administrative capability but also the strategic use of information technology to foster transparency, innovation, and citizen participation. This study explores the role of digital leadership in local governance by analyzing the use of social media platforms by the Denpasar City Government, namely Instagram (@denpasarkota), TikTok (@pemkotdenpasar), and the community-driven account @infodenpasar. Using a mixed-methods approach that combines content analysis and comparative assessment of engagement metrics, the research examines how these platforms function as instruments of communication, legitimacy-building, and participatory governance. The findings reveal that while official government accounts emphasize policy dissemination, public service announcements, and cultural promotion, community-based platforms such as @infodenpasar demonstrate higher levels of interaction and responsiveness, thereby acting as complementary channels in the governance ecosystem. The study contributes theoretically by expanding the discourse on digital leadership and social media governance in local contexts, and practically by offering insights for municipal governments in developing more collaborative and innovative digital communication strategies to enhance public trust and engagement.